2016
DOI: 10.1007/s00122-016-2707-1
|View full text |Cite
|
Sign up to set email alerts
|

Fine mapping and candidate gene analysis of the dominant glandless gene Gl 2 e in cotton (Gossypium spp.)

Abstract: Dominant glandless gene Gl 2 (e) was fine-mapped to a 15 kb region containing one candidate gene encoding an MYC transcription factor, sequence and expression level of the gene were analyzed. Cottonseed product is an excellent source of oil and protein. However, this nutrition source is greatly limited in utilization by the toxic gossypol in pigment glands. It is reported that the Gl 2 (e) gene could effectively inhibit the formation of the pigment glands. Here, three F2 populations were constructed using two … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 32 publications
0
29
0
Order By: Relevance
“…Studies on glandless mutants showed that a Val for Ala amino acid substitution at residue 43 of Gl 2 results in the dominant Gl 2 e allele, while single nucleotide insertions into Gl 2 and Gl 3 introduce premature stop codons and generate the recessive gl 2 and gl 3 alleles (Ma et al , ). Later, Cheng et al () confirmed the identity of GoPGF using near‐isogenic lines (NILs) at the Gl 2 e locus. Comparative transcriptome analysis of glanded and glandless cotton embryos identified three Cotton Gland Formation ( CGF ) genes that participate in gland formation (Janga et al , ).…”
Section: Introductionmentioning
confidence: 99%
“…Studies on glandless mutants showed that a Val for Ala amino acid substitution at residue 43 of Gl 2 results in the dominant Gl 2 e allele, while single nucleotide insertions into Gl 2 and Gl 3 introduce premature stop codons and generate the recessive gl 2 and gl 3 alleles (Ma et al , ). Later, Cheng et al () confirmed the identity of GoPGF using near‐isogenic lines (NILs) at the Gl 2 e locus. Comparative transcriptome analysis of glanded and glandless cotton embryos identified three Cotton Gland Formation ( CGF ) genes that participate in gland formation (Janga et al , ).…”
Section: Introductionmentioning
confidence: 99%
“…T582 serves as a basic tool for scientific study into the mechanism of cotton metabolism, inheritance and development due to its multiple recessive marker stocking with cu, fg, cl 1 , gl 1 , and v 1 (Kohel et al 1965). The candidate gene of the pigment glands which related gene gl 1 would provide the prospects of fabricating gossypol-free cotton seeds (Cheng et al 2016). In addition, many important genes were subdivided into different linkage groups through T582 (Percival and Kohel 1974;Endrizzi et al 1984).…”
Section: Discussionmentioning
confidence: 99%
“…, 15 s at 95°C (Cheng et al 2016). qRT-PCR was carried out by the gene-specific primers (5′-ATTGCCACT GTCATCCCCAACTGCT-3′, 5′-TCAGCTGAAAACCT CATAGAATTTC-3′) and actin (Genbank ID: AY305733) (5′-ATCCTCCGTCTTGACCTTG-3′, 5′-TGTCCGTCA GGCAACTCAT-3′) was employed as an internal control.…”
Section: Quantitative Reverse Transcription-pcr (Qrt-pcr) Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, it is also crucial to fine map the genomic regions with large number of markers that will enhance the efficiency of selection, which ultimately helps to clone the genes present at the target loci. In cotton, fine mapping of few important genes and QTLs has been reported, that is fine mapping of glandless gene (Cheng et al ., ), leaf shape (Andres et al ., ) and fibre quality‐related QTLs (Fang et al ., ; Liu et al ., ; Xu et al ., ).…”
Section: Gene Discovery Tools Recently Availablementioning
confidence: 99%